Low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on high-carbon design and preparation method thereof
By adding Nb elements to the 2000MPa-grade thermoformed steel to form nanoprecipitate NbC, and combining with a specific process flow, the problems of complex and high cost in the prior art are solved, and the excellent hydrogen embrittlement resistance and the effect of reducing production costs of the thermoformed steel is achieved.
Patent Information
- Application Number
- CN202411182947.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The existing 2000MPa grade low-hydrogen embrittlement thermoforming steel has complex processes and high production costs, making it difficult to reduce costs while improving the anti-hydrogen embrittlement performance.
Using low-carbon matrix thermoformed steel based on high-carbon design, nanoprecipitates NbC are formed by adding Nb elements. Combined with specific hot rolling, coiling, annealing and thermoforming processes, the particle size and distribution of nanoprecipitates are controlled, and the grains are refined to improve the anti-hydrogen embrittlement properties.
It has achieved excellent hydrogen embrittlement resistance of 2000MPa grade thermoformed steel, reducing alloy costs and production costs, and simplifying the process flow, which is suitable for promotion and application.
Smart Images

Figure CN119061330B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal processing, and in particular relates to a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design and a preparation method thereof. Background Art
[0002] With the upgrading of the global automobile industry and the overall rise of new energy vehicles in China, the steel used in automobile materials is gradually developing in the direction of high strengthening and light weight, and the application of high-strength steel, advanced high-strength steel or ultra-high-strength steel is becoming more and more widespread. Low-carbon MnB steel plate is one of the most widely used hot-formed steels. After die-cutting and quenching, its structure is uniform martensite with high tensile strength, usually between 1100 and 1800 MPa; in addition, some companies have also developed hot-formed steel with a tensile strength of 2000 MPa, which is mainly used in key safety parts of automobiles, such as A-pillars, B-pillar reinforcement plates and other locations.
[0003] As we all know, as the strength of hot-formed steel continues to increase, especially when it exceeds 1500MPa, its hydrogen embrittlement phenomenon will become particularly obvious. Hydrogen embrittlement is caused by the adsorption and diffusion of hydrogen inside the steel, which may occur during pickling, electroplating, hot forming, service, etc. Once hydrogen is absorbed into the steel, it will cause embrittlement of the lattice, making the steel easy to break. The structure of hot-formed steel is generally a full martensitic structure, which increases the strength and hardness of the steel, but also increases the grain boundaries and phase boundaries, providing more crack propagation paths, and increasing the possibility of hydrogen embrittlement. In addition, due to the complex lattice structure of martensitic steel, there are many microscopic defects and phase interfaces, which can promote the adsorption and diffusion of hydrogen atoms, resulting in an increase in the concentration of hydrogen and an increase in the risk of hydrogen embrittlement. Secondly, martensitic steel is usually used in high-strength and high-stress engineering applications, and there are large stress concentration areas in these application scenarios. Hydrogen atoms tend to aggregate under high stress to form hydrogen atom clusters, which further weaken the toughness and ductility of the steel, thereby increasing the probability of hydrogen embrittlement. Therefore, hydrogen embrittlement has always affected the research and development of 2000MPa ultra-high strength steel plates. How to improve the hydrogen embrittlement resistance of 2000MPa hot-formed steel is a topic of great concern to relevant scholars at home and abroad.
[0004] The invention patent with patent number CN202311215441.9 discloses a 2000MPa grade delayed cracking resistant hot-formed steel and its production method, which uses nickel-niobium-copper composite microalloying, and its components are C: 0.20%~0.40%, Si: 0.20%~0.80%, Mn: 0.5%~1.5%, P≤0.006%, S≤0.004%, Als: 0.050%~0.085%, Cr: 1.0%~1.5%, Ni: 0.50%~0.80%, Ti: 0.020%~0.050%, Nb: 0.020%~0.050%, Cu: 0.20%~0.40%; B: 0.002%~0.005%, and the rest are Fe and unavoidable impurity elements. Its tensile strength after hot forming is greater than 2000MPa, the elongation is greater than 6%, the hydrogen embrittlement sensitivity during SSRT slow strain stretching is less than 50%, and the hydrogen embrittlement resistance is excellent. However, the addition of 0.5% to 0.8% Ni increases the alloy cost of the product; in addition, after the steel plate is flattened, it needs to undergo a dehydrogenation treatment process with a heating temperature of 200 to 250°C and a holding time of 100 to 150 minutes, which increases the production cost.
[0005] The invention patent with patent number CN117737372A discloses a 2.0GPa grade Cu-containing hot-formed steel plate and its preparation method, which uses copper-niobium-vanadium-molybdenum composite microalloying and performs aging-quenching heat treatment. Its components are C: 0.33%~0.35%, Si: 0.6~0.8%, Mn: 1.9~2.1%, B: 0.002~0.003%, Cu: 0.09~0.11%, Cr: 1.9~2.1%, Mo: 0.19~0.21%, Nb: 0.045~0.056%, Ti: 0.02~0.03%, V: 0.055~0.065%, Al: 0.025~0.035%, S≤0.02%, P≤0.01%, and the rest are Fe and unavoidable impurity elements. Its hot-formed steel plate has good strength and toughness, with a tensile strength greater than 2150MPa and an elongation greater than 7%, but the addition of 0.19-0.21% Mo, 1.9-2.1% Mn and 1.9-2.1% Cr increases the alloy cost of the product; in addition, the aging-quenching heat treatment process is difficult to control, has high requirements on equipment, and has high production costs.
[0006] How to improve the hydrogen embrittlement resistance of 2000MPa hot-formed steel while reducing production costs is a common pursuit of people in this field. Summary of the invention
[0007] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on high-carbon design and a preparation method thereof, aiming to solve the problem that the existing 2000MPa grade low hydrogen embrittlement hot-formed steel has complex process and high production cost.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] A 2000MPa hydrogen embrittlement resistant hot-forming steel with a low carbon matrix based on a high carbon design, wherein the hot-forming steel contains nano-precipitates NbC after hot-forming, and the ratio α of the Nb content in the form of the nano-precipitates to the initial Nb addition amount satisfies: 86%≤α≤93%; and the content of solid-solution carbon in the martensite matrix after hot-forming C 终 and the initial carbon content C 初 Satisfy: 0.85≤C 终 / C 初 ≤0.95.
[0010] In certain specific embodiments, the size t of the nano-precipitates NbC satisfies: the proportion of those in the range of 60-140 nm is greater than 80%, and the average size d of the original austenite grains of the hot-formed steel after hot-forming satisfies: d≤9 μm.
[0011] The main purpose of the present invention is to provide a preparation method of a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design, including smelting, casting, hot rolling, coiling, pickling, cold rolling, continuous annealing and hot forming. The process parameters of the hot rolling process are: the starting rolling temperature is 1050-1200°C, and the final rolling temperature is 850-910°C.
[0012] In some specific embodiments, the following components are included in mass percentage: C: 0.32-0.36%, Mn: 1.20-1.60%, S≤0.003%, P≤0.020, Si: 0.40-0.80%, Als: 0.02-0.06%, Ti: 0.02-0.06%, B: 0.0020-0.0040%, Cr: 0.2-0.6%, Nb: 0.10-0.15%, and 2.4≤C / Nb≤3.20, and the rest are Fe and unavoidable impurity elements.
[0013] In some specific embodiments, the process parameters of the coiling process are: the coiling temperature is 600-670°C.
[0014] In some specific embodiments, the process parameters of the annealing step are: the continuous annealing temperature is 760-830°C.
[0015] In some specific embodiments, the thermoforming process is specifically as follows: in an air or nitrogen protective atmosphere, the thermoforming temperature is 890-940° C., and the temperature is kept for 3-5 minutes.
[0016] Furthermore, the thermoforming process is specifically as follows: in an air or nitrogen protective atmosphere, the thermoforming temperature is 900° C. and the temperature is kept for 4 minutes.
[0017] In some specific embodiments, a coating process is further included, wherein the coating process is to coat the hot-formed steel after continuous annealing, wherein the coating includes an AlSi coating and a zinc coating, and the coating process dew point is controlled below -20°C.
[0018] Compared with the prior art, the present invention has at least the following advantages:
[0019] 1) The low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on high-carbon design provided by the present invention is prepared by adding Nb element: first, Nb element will form a large number of nano-scale carbides NbC during hot rolling, coiling and other processes, and the nano-precipitates NbC will form hydrogen traps to adsorb free hydrogen atoms in the hot-formed steel, prevent the diffusion and focusing of hydrogen, thereby improving the hydrogen embrittlement resistance of the hot-formed steel; in addition, the addition of Nb element can refine the grains, increase the grain boundaries, make the unit grain boundary stress, dislocation, and hydrogen distribution more uniform, thereby further improving the hydrogen embrittlement resistance of the hot-formed steel; and after the grains are refined, the toughness can be improved, the deformation of the hot-formed steel can be increased, and the strength of the hot-formed steel can be improved.
[0020] 2) The hot-formed steel of the present invention, by adding Nb element and controlling the mass ratio of C / Nb, combined with specific hot rolling, coiling, annealing, and hot forming processes, makes the ratio α of the Nb content existing in the form of nano-precipitates NbC to the initial Nb addition amount after hot forming satisfy: 86%≤α≤93%; the size t of the nano-precipitates NbC satisfies: the proportion of those located in the range of 60 to 140 nm is greater than 80%. According to current research, the semi-coherent / incoherent interface between large particles and the matrix has stronger hydrogen desorption energy, which is one of the key elements for the excellent hydrogen embrittlement resistance of this steel; and the average size d of the original austenite grains after hot forming satisfies: d≤9μm; and the carbon content C in the final matrix of the hot-formed steel satisfies: 终 and the initial carbon content C 初 Satisfy: 0.85≤C 终 / C 初 ≤0.95, so that the final hot-formed steel has a yield strength of ≥1300MPa, a tensile strength of ≥1900MPa, an elongation of ≥6%, and an ultimate tip cold bending angle of ≥50°. It does not crack after being immersed in a 0.1mol / L hydrochloric acid aqueous solution with a concentration of 1.1 times the yield strength for 300h, and has excellent resistance to hydrogen embrittlement.
[0021] 3) The preparation method of the low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on high-carbon design provided by the present invention adds an appropriate amount of low-cost Nb element, thereby reducing the alloy cost of the hot-formed steel; no additional dehydrogenation treatment process or complex and demanding aging-quenching treatment process is required, thereby reducing the production cost; that is, the preparation method of the present invention has easy-to-obtain raw materials, low cost, simple and easy-to-implement process, high repeatability, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0023] Figure 1 The process flow chart of the low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on high-carbon design provided by the present invention;
[0024] Figure 2 This is the X-ray diffraction spectrum of the hot-formed steel prepared in Example 5 of the present invention;
[0025] Figure 3 The TEM microscopic characterization results of the hot-formed steel prepared in Example 5 of the present invention are shown in Figure A, where Figure A is a density statistical result diagram and Figure B is a size statistical result diagram;
[0026] Figure 4 This is an EBSD observation result diagram of the original austenite crystal of the hot-formed steel prepared in Example 5 of the present invention;
[0027] Figure 5 This is a real picture of the hot-formed steel in Example 5 of the present invention after being stamped into a hot-formed part;
[0028] Figure 6 for Figure 5 Metallographic photograph of hot formed parts. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0030] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0031] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0032] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0033] In the following embodiments, metallographic structure reliability: tested in accordance with "GB / T 13298-1991 Metal Microstructure Test Method"; mechanical property reliability: tested in accordance with "GB / T228.1-2010 Metal Material Tensile Test Part 1: Room Temperature Test Method"; cold bending performance reliability: tested in accordance with "T / CSAE 154-2020 Ultra-High Strength Automobile Steel Plate Ultimate Tip Cold Bending Performance Test Method"; hydrogen embrittlement resistance reliability: tested in accordance with "T / CSAE 155-2020 Ultra-High Strength Automobile Steel Plate Hydrogen Induced Delayed Fracture Sensitivity U-shaped Constant Bending Load Test Method".
[0034] The 2000MPa grade ultra-high strength and hydrogen embrittlement resistant hot-formed steel provided in the present application includes the following components in mass percentage: C: 0.32-0.36%, Mn: 1.20-1.60%, S≤0.003%, P≤0.020, Si: 0.40-0.80%, Als: 0.02-0.06%, Ti: 0.02-0.06%, B: 0.0020-0.0040%, Cr: 0.2-0.6%, Nb: 0.10-0.15%, and 2.4≤C / Nb≤3.20, and the rest are Fe and unavoidable impurity elements.
[0035] The main components are:
[0036] C: C is a strong solid solution strengthening element, which plays a decisive role in obtaining ultra-high strength. If the C content is too low, it is difficult to ensure the strength of the steel. If the C content is too high, a large amount of pearlite, bainite, and martensite will be easily formed during the cooling process after fine rolling. The higher the C content, the higher the strength, which will cause the plasticity to decrease. If the C content is too high, the welding performance will be reduced and the delayed cracking sensitivity will be increased. Therefore, the C content is controlled at 0.32-0.36%.
[0037] Mn: As one of the important austenite-forming elements, Mn can expand the austenite (γ) phase region, reduce the Ms point of steel, and reduce the phase transition temperature from γ to α through solid solution strengthening, which is conducive to obtaining a large amount of metastable residual austenite at room temperature. In addition, the Mn element also increases the stability of supercooled austenite and the hardenability of steel, thereby significantly improving the strength of steel. However, too high a Mn content will have an adverse effect on steel, such as increasing the probability of the appearance of banded structure in steel. Therefore, the Mn content is controlled at 1.20-1.60%.
[0038] Si: Si element can improve the hardenability of hot-formed steel and is the main alloying element of hot-formed steel. The Si content of the present application is controlled at 0.40-0.80%.
[0039] Cr: Cr is a medium-strong carbide-forming element. Adding a certain amount of Cr to steel can significantly improve the hardenability of the steel, and can also change the morphology and distribution of martensite under certain conditions, thereby improving the strength and plasticity of the steel. It is the main alloying element of hot-formed steel, but too high a Cr content will reduce the stability of the retained austenite and make carbides more likely to precipitate. The Cr content of this application is controlled at 0.2-0.6%.
[0040] Ti: Ti is one of the effective elements for refining austenite grains and improving delayed cracking resistance. Adding Ti to hot-formed steel can not only fix nitrogen in the steel, avoid the formation of BN, and hinder the segregation of B at the austenite grain boundary, thereby giving full play to the role of B in improving hardenability; but also the solid-solution Ti can improve the hardenability of steel, and if the Ti content is too high, excessive nano-TiC particles will be formed, reducing the content of solid-solution C elements in the martensite matrix after hot forming, and reducing the precipitation of NbC; the Ti content in this application is controlled at 0.02-0.06%.
[0041] Nb: Nb is one of the effective elements for improving hydrogen embrittlement resistance and is the key element studied in this application. In this application, Nb is a strong C and N compound forming element, which can play a role in refining austenite grains. Adding a small amount of Nb to steel can form a certain amount of Nb carbon and nitride, thereby hindering the growth of austenite grains and improving the mechanical properties of steel; in addition, Nb carbon and nitride are good hydrogen traps, which can effectively inhibit the diffusion of hydrogen in steel, which is beneficial to improving the delayed cracking resistance of steel; however, if the Nb content is too high, too much nano-precipitate NbC will form, which will lead to a decrease in the solid solution C content in the martensite matrix after hot forming, thereby reducing the strength of the steel; therefore, the Nb content in this application is controlled at 0.10-0.15%.
[0042] The 2000MPa grade ultra-high strength hydrogen embrittlement resistant hot-formed steel provided in the present application reduces or eliminates the occurrence of hydrogen embrittlement by adding Nb elements with hydrogen embrittlement resistance. The Nb element will form a large amount of nano-precipitates NbC during hot rolling, coiling and other processes, and the nano-precipitates NbC will form hydrogen traps to adsorb free hydrogen atoms in the hot-formed steel, prevent the diffusion and focusing of hydrogen, thereby providing the steel plate with hydrogen embrittlement resistance; at the same time, the addition of Nb elements can refine the grains, increase the grain boundaries, and make the unit grain boundary stress, dislocation, and hydrogen distribution more uniform, thereby further improving the hydrogen embrittlement resistance of the hot-formed steel; and after the grains are refined, the toughness can be improved, the deformation of the steel plate can be increased, and the strength of the hot-formed steel can be further improved.
[0043] Furthermore, the present invention reduces the content of solid-solution carbon in the martensite matrix after hot forming by adding Nb element, controlling the mass ratio of C / Nb, and specifying the heating temperature, coiling temperature and hot forming temperature. 终 and the initial carbon content C 初 The specific requirements are met, the ratio of the Nb content in the form of nano-precipitates NbC to the initial addition amount, and the specific particle size ratio of the nano-precipitates NbC, thereby preparing a hot-formed steel that takes into account both the strength of the hot-formed steel and the resistance to hydrogen embrittlement;
[0044] The preparation method of 2000MPa grade ultra-high strength hydrogen embrittlement resistant hot-formed steel provided in this application is as follows: Figure 1 As shown, the preparation method comprises the following steps:
[0045] (1) Smelting: Desulfurize the molten iron that meets the formula requirements and smelt it in a converter, and control the tapping temperature at 1600-1730°C;
[0046] In the following embodiments and comparative examples, the tapping temperature is controlled at 1650°C.
[0047] (2) Ingot casting: smelting in converter and casting into ingot, casting temperature 1500~1630℃, ingot thickness 230~260mm;
[0048] The pouring temperature in the following embodiments and comparative examples is 1580°C and the thickness of the cast billet is 240 mm;
[0049] (3) Hot rolling: the ingot is heated to 1200-1300°C, the heating rate is controlled at 300-400°C / h, the starting rolling temperature is 1050-1200°C, the final rolling temperature is controlled between 850°C and 910°C, and the hot rolled plate thickness is 3-5 mm;
[0050] In the following embodiments and comparative examples, the ingot was heated to 1250°C, the heating rate was controlled at 350°C / h, the starting rolling temperature was 1050-1200°C, the final rolling temperature was controlled between 850°C and 910°C, and the hot rolled plate thickness was 3-5 mm;
[0051] (4) Coiling: After hot rolling, laminar cooling is performed and then coiling is performed. The coiling temperature is controlled between 600 and 670 °C.
[0052] (5) Pickling: conventional pickling, pickling speed 250-300 m / min, pickling aqueous solution concentration 50-80%, water temperature 30-70°C, pickling time 3-5 min;
[0053] In the following examples and comparative examples, the pickling speed is 280 m / min, the concentration of the pickling aqueous solution is 75%, the water temperature is 50°C, and the pickling time is 5 min;
[0054] (6) Cold rolling: cold rolling is carried out immediately after pickling, with a total reduction rate of 50-60%, and the thickness of the steel plate after cold rolling is 1.0-1.8 mm;
[0055] In the following examples and comparative examples, the total reduction ratio is 60%, and the thickness of the steel plate after cold rolling is 1.6 mm;
[0056] (7) Continuous annealing: After cold rolling, continuous annealing is performed, the preheating temperature of the continuous annealing is controlled between 400 and 550° C., the annealing temperature is controlled between 760 and 830° C., and the annealing time is 3 to 10 minutes to obtain a steel plate with a thickness of 1.6 mm;
[0057] In the following embodiments and comparative examples, the preheating temperature is controlled between 400 and 550° C., the annealing temperature is controlled between 780° C., and the annealing time is 6 minutes;
[0058] (8) Hot forming: The steel plate obtained in step (7) is heated under a nitrogen atmosphere at a temperature between 890°C and 940°C for 3 to 5 minutes, and then the steel plate is taken out for quenching at a cooling rate between 25°C and 50°C / s (specifically 35°C / s) to obtain hot-formed steel.
[0059] Another preferred technical solution of the present invention is: it also includes a coating process, wherein the coating process is to coat the hot-formed steel after continuous retreat, wherein the coating includes an AlSi coating and a zinc coating, and the coating process dew point is controlled below -20°C; the coating process can effectively prevent the hot-formed steel from being oxidized at high temperature during the heating process.
[0060] Among them, this scheme controls the hot rolling start temperature to 1050-1200°C, and the final rolling temperature is set to 850-910°C. A low final rolling temperature can increase the precipitation rate of Nb, but too low a temperature will affect the hot rolling quality; conversely, a high final rolling temperature will reduce the precipitation rate of Nb;
[0061] Furthermore, the coiling temperature is set to 600-670°C. A low coiling temperature can further increase the precipitation of Nb, but a too low coiling temperature will increase the strength of the steel coil and cause surface cracking in the subsequent acid rolling process; on the contrary, a high coiling temperature will affect the precipitation of Nb.
[0062] Furthermore, the continuous annealing temperature is set at 760-830°C. A low continuous annealing temperature cannot reduce the strength of the continuously annealed plate and cannot play the role of continuous annealing. On the contrary, a high continuous annealing temperature will austenitize the steel plate and increase the size of the original austenite grains.
[0063] Furthermore, the heating temperature is set to 890-940°C and the holding time is 3-5 minutes. If the heating temperature is too low or the time is too short, the full martensite structure will not be formed after hot forming, affecting the strength of the steel. On the contrary, if the heating temperature is too high or the time is too long, the original austenite grain size will be too large, resulting in reduced hydrogen embrittlement resistance.
[0064] 1. Example and surface quality
[0065] Examples 1-8
[0066] Examples 1-8 are 2000MPa grade ultra-high strength hydrogen embrittlement resistant hot-formed steels. The raw material composition and proportion of each example, as well as the specific process parameters in the preparation method are shown in Table 1 and Table 2, by weight percentage:
[0067] Comparative Examples 1-13
[0068] Comparative Examples 1-13 are respectively 2000MPa grade ultra-high strength hydrogen embrittlement resistant hot-formed steels. The composition and proportion of the raw materials of each comparative example, certain process parameters in the preparation method (unspecified raw materials and / or process parameters are the same for each embodiment and comparative example) and the surface quality after hot forming are listed in Table 1; (the preparation method of Comparative Examples 1-13 is the same as that of Example 5, and the differences are shown in Table 1 and Table 2):
[0069] Table 1 Component ratio of hot-formed steel in each embodiment and comparative example (wt.%)
[0070]
[0071]
[0072] Table 2 Process parameters of hot-formed steel in various embodiments and comparative examples
[0073]
[0074]
[0075] At the same time, the performance tests were carried out on the hot-formed steels prepared in Examples 1-5 and Comparative Examples 1-13 of the present application, specifically:
[0076] Table 3 C 终 The precipitation rate of NbC was obtained by electrolytic extraction. The specific operation method was: using 1% lithium chloride + 10% acetylacetone methanol solution and a current density of 0.04-0.06A / cm 2, the electrolysis conditions of the ambient temperature of 0 to -5 ° C are used to extract the second phase precipitate, the electrolysis residue is collected and washed, and the dry powder is subjected to X-ray diffraction analysis to obtain the precipitate phase structure. The electrolysis residue is placed in a polytetrafluoroethylene beaker, and hydrochloric acid, nitric acid and hydrofluoric acid are added to dissolve the sample, and then diluted with water to a 100 mL polytetrafluoroethylene volumetric flask to make up the volume. The content of each element in the precipitate, including Nb and C elements, can be determined by ICP-AES (inductively coupled plasma atomic emission spectrometry). Part of the test results of Example 5 are shown as follows Figure 2 As shown;
[0077] The proportion of precipitate NbC with a size t of 60 to 140 nm is obtained by SAXS (small angle X-ray scattering), which is performed by irradiating the X-ray beam at different angles (usually between 0.1 and 10 degrees) onto the extracted powder, collecting the X-rays scattered by the powder, and analyzing the results to determine the particle size distribution; the number density of the precipitate ρ 析 The density was calculated by TEM (projection electron microscope) microstructure characterization method. Figure 3 As shown; the average size d of the original austenite grains can be obtained by EBSD (electron backscatter diffraction technology), wherein the EBSD observation results of Example 5 are as follows Figure 4 The performance test results of various embodiments and comparative examples are shown in Table 3:
[0078] Table 3 Microstructure characterization results of hot-formed steel
[0079]
[0080]
[0081] Note: α is the ratio of the Nb content in the form of nano-precipitates in hot-formed steel after hot-forming to the initial addition;
[0082] The present application performs performance tests on the mechanical properties and hydrogen embrittlement resistance of the hot-formed steels in Examples 1-8 and Comparative Examples 1-13, and the results are shown in Table 4:
[0083] Table 4 Mechanical properties and hydrogen embrittlement resistance of steel plates
[0084]
[0085]
[0086] Note: In Table 4, the yield strength of Examples 1-8 is greater than 1300MPa, the tensile strength is greater than 1900MPa, the elongation after fracture is greater than 6%, the ultimate tip cold bending is above 50°, and the hydrogen embrittlement resistance is 1.1 times the yield strength, and there is no cracking after immersion in 0.1mol / L hydrochloric acid aqueous solution for 300h. All test results that meet the target value are marked with ○, and those that do not meet the target value are marked with ×.
[0087] According to the test data in Tables 3 and 4, the hot-formed steel provided in the present application has excellent mechanical properties and hydrogen embrittlement resistance. Specifically, its yield strength is ≥1300MPa, tensile strength is ≥1900MPa, elongation is ≥6%, and the ultimate tip cold bending angle is ≥50°. It does not crack after being immersed in a 0.1 mol / L hydrochloric acid aqueous solution with a concentration of 1.1 times the yield strength for 300 hours; its hot-formed products can be used for safety parts and structural parts of passenger cars, which can reduce the weight of the body in white.
[0088] From the comparison between Example 5 and Comparative Examples 1-6, it can be seen that in Comparative Example 1, the C content is lower than the required range, the Nb content is within the range, and the C / Nb ratio is lower than the required range, which ultimately leads to C 终 / C 初 The result is that the strength is low and the strength is unqualified; in Comparative Example 2, the C content is within the required range, the Nb content is lower than the required range, and the C / Nb ratio is higher than the required range, which ultimately leads to C 终 / C 初 The ratio of C / Nb in the comparative example 3 is lower than the required range, and the ratio of NbC in the range of 60-140 nm is lower than the required range, resulting in unqualified hydrogen embrittlement resistance. 终 / C 初 The result is that the strength is low and the strength is unqualified; in Comparative Example 4, the C content is within the required range, the Nb content is within the required range, and the C / Nb ratio is higher than the required range, which ultimately leads to C 终 / C 初 The ratio of C / Nb in the comparative example 5 is higher than the required range, the ratio of Nb in the comparative example 6 is within the required range, and the ratio of C / Nb is within the required range. 终 / C 初 The ratio of C / Nb in the comparative example 6 is within the required range, the ratio of Nb in the comparative example 6 is higher than the required range, and the ratio of C / Nb is lower than the required range, which ultimately leads to the failure of the hydrogen embrittlement resistance. 终 / C 初In summary, the preparation method of the present application makes the yield strength of the hot-formed steel ≥1300MPa, the tensile strength ≥1900MPa, the elongation ≥6%, and the ultimate tip cold bending angle ≥50°, and it does not crack when immersed in a hydrochloric acid aqueous solution of 1.1 times the yield strength and 0.1 mol / L for 300 hours, and has excellent hydrogen embrittlement resistance. The ratio of the content of dissolved carbon in the martensitic matrix after hot forming to the content of initially added carbon, the ratio of the content of Nb in the form of nano-precipitates to the initially added amount, the specific particle size ratio of nano-precipitates NbC, and the average size of the original austenite grains all meet the specific requirements of hot-formed steel; it is related to the ratio of C and Nb elements, as well as the C / Nb ratio. When the ratio of C and Nb elements, as well as the C / Nb ratio are too high or too low, the mechanical properties and hydrogen embrittlement resistance of the hot-formed steel will be greatly affected, and the relevant requirements cannot be met.
[0089] From the comparison between Example 5 and Comparative Examples 7-13, it can be seen that in Comparative Example 7, the raw material components of the hot-formed steel are within the range (the slight differences in the components of the raw materials in the comparative examples are all within the error range, and it can be regarded as the same raw material composition for processing), the high starting rolling temperature leads to an excessively high final rolling temperature, which reduces the precipitation of NbC and causes C 终 / C 初 The proportion of NbC size of 60-140nm is too high, resulting in unqualified hydrogen embrittlement resistance; in Comparative Example 8, the raw material components of the hot-formed steel are within the range, the starting and final rolling temperatures are normal, but the coiling temperature is too high, which reduces the precipitation of NbC and causes C 终 / C 初The ratio of NbC size of 60-140nm is too high, and the ratio of NbC size of 60-140nm is too low, resulting in unqualified hydrogen embrittlement resistance; in Comparative Example 9, the various raw material components of the hot-formed steel are within the range, the start rolling temperature, the final rolling temperature and the coiling temperature are normal, but the annealing temperature is too high, resulting in the growth of the original austenite grains, and ultimately resulting in unqualified hydrogen embrittlement resistance; in Comparative Example 10, the various raw material components of the hot-formed steel are within the range, the start rolling temperature, the final rolling temperature, the coiling temperature and the annealing are normal, but the heating temperature is too high, resulting in the growth of the original austenite grains, and ultimately resulting in unqualified hydrogen embrittlement resistance; in Comparative Example 11, the various raw material components of the hot-formed steel are within the range, the start rolling temperature, the final rolling temperature The temperature, coiling temperature and annealing temperature are normal, but the heating temperature is too low, resulting in the final structure not being full martensite, resulting in low strength and failure; in Comparative Example 12, the raw material components of the hot-formed steel are all within the range, the start rolling temperature, the final rolling temperature, the coiling temperature, the annealing temperature and the heating temperature are normal, but the heating time is too long, resulting in the growth of the original austenite grains, and ultimately resulting in unqualified hydrogen embrittlement resistance; in the comparative example, the raw material components of the hot-formed steel are all within the range, the start rolling temperature, the final rolling temperature, the coiling temperature, the annealing temperature and the heating temperature are normal, but the heating time is too short, resulting in the final structure not being full martensite, resulting in low strength and failure;
[0090] By comparing Example 5 with Comparative Examples 7-13, it can be seen that in the hot-formed steel of the present application, within a specific composition and ratio range, combined with specific process parameters (start rolling temperature, final rolling temperature, coiling temperature, annealing temperature, heating temperature and heating time, etc.), the content of solid dissolved carbon in the martensite matrix after hot forming is C 终 and the initial carbon content C 初 The specific requirements are met, the ratio of the Nb content in the form of nano-precipitates NbC to the initial addition amount, the specific particle size ratio of the nano-precipitates NbC, and the original austenite crystal size after hot forming reach the best optimization value, so that the hot-formed steel has both excellent mechanical properties and hydrogen embrittlement resistance; when the process parameter values in the preparation method (start rolling temperature, final rolling temperature, coiling temperature, annealing temperature, heating temperature and heating time, etc.) are not within the ratio range of the present application, both mechanical properties and hydrogen embrittlement resistance cannot be achieved; that is, the components, proportions and process parameters in the hot-formed steel in the present application work synergistically, and their combined effect makes the hot-formed steel have excellent mechanical properties (2000MPa level) and hydrogen embrittlement resistance.
[0091] This application takes Example 5 as an example, and conducts hot forming part trial production of the prepared 2000MPa ultra-high strength hydrogen embrittlement resistant hot forming steel. Figure 5 As shown, the performance test results of the hot formed parts are as follows: yield strength 1358MPa, tensile strength 1944MPa, elongation after fracture 6.7%, and its metallographic structure is as follows Figure 6 As shown, it is a full martensitic structure, and after hot forming, the parts are left stationary for 10 days without hydrogen embrittlement and cracking. All performances meet the requirements of the automobile factory.
[0092] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on high-carbon design, characterized in that: The hot-formed steel contains nano-precipitates NbC after hot forming, and the ratio α of the Nb content in the form of the nano-precipitates to the initial Nb addition amount satisfies: 86%≤α≤93%; and the content of solid-solution carbon C in the martensite matrix after hot forming is 终 and the initial carbon content C 初 Satisfy: 0.85≤C 终 / C 初 ≤0.95; the size t of the nano-precipitate NbC satisfies: the proportion of the nano-precipitate in the range of 60-140nm is greater than 80%, and the average size d of the original austenite grains of the hot-formed steel after hot forming satisfies: d≤9μm.
2. A method for preparing a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design according to claim 1, comprising smelting, billet casting, hot rolling, coiling, pickling, cold rolling, continuous annealing and hot forming, characterized in that: The process parameters of the hot rolling process are: the starting rolling temperature is 1050-1200°C, and the final rolling temperature is 850-910°C.
3. The method for preparing a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design according to claim 2, characterized in that: The alloy includes the following components in mass percentage: C: 0.32-0.36%, Mn: 1.20-1.60%, S≤0.003%, P≤0.020, Si: 0.40-0.80%, Als: 0.02-0.06%, Ti: 0.02-0.06%, B: 0.0020-0.0040%, Cr: 0.2-0.6%, Nb: 0.10-0.15%, and 2.4≤C / Nb≤3.2, and the rest are Fe and unavoidable impurity elements.
4. The method for preparing a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design according to claim 2, characterized in that: The process parameters of the coiling process are: the coiling temperature is 600-670°C.
5. The method for preparing a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design according to claim 4, characterized in that: The process parameters of the continuous annealing process are as follows: the continuous annealing temperature is 760-830°C.
6. The method for preparing a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design according to claim 5, characterized in that: The thermoforming process is specifically as follows: in an air or nitrogen protective atmosphere, the thermoforming temperature is 890-940° C. and the temperature is kept for 3-5 minutes.
7. The method for preparing a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design according to claim 6, characterized in that: The thermoforming process is specifically as follows: in an air or nitrogen protective atmosphere, the thermoforming temperature is 900° C. and the temperature is kept for 4 minutes.
8. The method for preparing a low-carbon matrix 2000MPa hydrogen embrittlement resistant hot-formed steel based on a high-carbon design according to claim 2, characterized in that: The method further comprises a coating process, wherein the coating process is to coat the hot-formed steel after continuous annealing, wherein the coating comprises an AlSi coating and a zinc coating, and the coating process dew point is controlled below -20°C.
Citation Information
Patent Citations
Method for testing and evaluating hydrogen embrittlement resistance of high-strength steel plate material
CN117347582A
2.0 GPa grade Cu-containing hot forming steel plate and preparation method thereof
CN117737372A
High-strength hot-formed steel sheet member
CN106103782A
Steel sheet for cans and method for producing same
CN106605006A